2014
DOI: 10.1007/s11011-014-9575-7
|View full text |Cite
|
Sign up to set email alerts
|

“Polymorphisms in folate metabolism genes as maternal risk factor for neural tube defects: an updated meta-analysis”

Abstract: Epidemiological studies have evaluated the association between maternal methylenetetrahydrofolate reductase (MTHFR) C677T, A1298C and methionine synthase reductase (MTRR) A66G polymorphisms and risk of neural tube defects (NTDs) in offspring. However, the results from the published studies on the association between these three polymorphisms and NTD risk are conflicting. To derive a clearer picture of association between these three maternal polymorphisms and risk of NTD, we performed meta-analysis. A comprehe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 89 publications
1
41
1
1
Order By: Relevance
“…Because of the large sample sizes, metaanalysis has more statistical power than a single study to obtained reliable result. Several large-scale meta-analyses combining data from multiple studies have been published investigating the association between MTHFR C677T polymorphism and various disease/disorders such as- Down syndrome [66], Neural Tube defects [67], cleft lip with/without palate [68], congenital heart defects [69], stroke [70], diabetes mellitus [71], Alzheimers disease [72], schizophrenia [73] and cancer [74].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the large sample sizes, metaanalysis has more statistical power than a single study to obtained reliable result. Several large-scale meta-analyses combining data from multiple studies have been published investigating the association between MTHFR C677T polymorphism and various disease/disorders such as- Down syndrome [66], Neural Tube defects [67], cleft lip with/without palate [68], congenital heart defects [69], stroke [70], diabetes mellitus [71], Alzheimers disease [72], schizophrenia [73] and cancer [74].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of the MTHFR 677TT genotype varies across ethnic groups and regions, ranging from ,2% in West African and African American populations (8,9) to .35% in some populations such as the northern Chinese and individuals of Mexican descent (8)(9)(10). Meta-analyses reported that mothers or infants with the TT genotype have significantly greater odds of a neural tube defect-affected pregnancy than do those with the CC genotype (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies later demonstrated similar independent associations between specific maternal genes and offspring phenotype without any transmission of the particular gene [168][169][170][171][172][173][174][175][176][177][178][179]. It was shown that maternal mutations of relevant genes involved in folate metabolism are associated with an increased risk for neural tube or congenital heart defects [170][171][172]. Similar findings were demonstrated for maternal polymorphisms involved in glucose metabolism [173].…”
Section: Interaction Of Parental Genes Parental Environment and Fetamentioning
confidence: 65%